Acronema crassifolium sp. nov. (Apiaceae), a distinct new species from Yunnan, southwest China - Wang, Huan-Chong; Zhou, Xin-Mao; Sun, Hang; Wang, Yue-Hua (Phytotaxa, 2013)
Acronema crassifolium, a distinct new species endemic to Yunnan province, China, is described and illustrated. It is characterized by its thickly papery, ternate, abaxially dark purple leaves, terminal umbels with 8–13 rays, and absent calyx teeth. The pollen morphology of the new species is also described in this study.